CARCASS QUALITY, MARBLING AND CHOLESTEROL CONTENT OF MALE BALI CATTLE FED FERMENTED COCOA SHELL - Suryanto, E.; Bulkaini, B.; Ashari, A.; Karda, I . W. (Journal of the Indonesian Tropical Animal Agriculture, 2014)
The experiment was conducted to evaluate the effect of fermented cacao shell on the carcassquality, percentage of non carcass components, marbling and cholesterol content of Bali cattle. NineBali cattle of 1.5-2 year old and 165-175 kg weight were grouped into three feeding trials. The firstgroup P0 was fed ration containing 30% cacao shell fermented with its own microorganism and 70%corn straw, the second group P1 was fed ration containing 30% cacao shell fermented with ruminal fluidand 70% corn straw, and the third group P2 was fed ration containing 30% cacao shell fermented withBioplus and 70% corn straw. All cattle were also given commercial concentrate amounting to 1% oftheir bodyweight. The cattle were slaughtered at the end of feeding trial and their carcasses, meat andnon carcass components were analysed. Experimental design used was completely randomized design.The results showed that carcass percentage, back fat thickness, rib eye area and meat index of Bali cattle were as follows group PO 53.33%, 3.08 mm, 59.65 cm2, 0.79%; group P1 52.64%, 5.31 mm, 58.52 cm,0.82% and group P2 5.32%, 5.7 mm, 57.75 cm, 0.79%, respectively. The marbling and cholesterolcontent of Bali beef were group PO 2.65% and 71.25 mg/100g, group P1 2.12% and 48.75 mg/100g,and P2 2.63% and 74.50 mg/100g. It could be concluded that fermented cacao shell could be used asfeed ingredient without any effect on the carcass and meat quality, marbling and cholesterol contents ofmale Bali beef.